Physician leadership development: towards multidisciplinary programs?. Issue 3 (27th September 2018) - Frich, Jan C; Spehar, Ivan
Abstract : Background: The format and content of leadership development programmes for physicians is a theme for discussion in the literature. Objectives: The aim of this study is to explore healthcare executives' perspectives on physician leadership development, focusing on perceived benefits and negative effects associated with multidisciplinary programmes. Methods: We did a qualitative study based on data from semistructured interviews with 16 healthcare executives in US healthcare systems. Results: We found that one group perceived programmes targeting one profession as advantageous, promoting openness and professional relationships among peers. Other executives argued that multidisciplinary programmes could add value because they could bridge professional boundaries, strengthen networks and build leadership capacity throughout an organisation. Costs, timing, organisational culture and a lack of knowledge about how to run multidisciplinary programmes were challenges our informants associated with multidisciplinary leadership development programmes. Conclusion: This study identifies topics and challenges that can inform organisational policies and decisions about leadership development activities.